Temporary Layoffs with Incomplete Worker Attachment in Search Equilibrium - Zaharieva, Anna (My University, 2010)
This paper revisits the no-attachment assumption in job search models with random productivity fluctuations and Nash-bargaining. Both workers and firms value the option to remain in attachment: firms profit from a reduced hiring cost, while workers gain from a higher reservation wage when bargaining with a new employer. Ex-post differentiation of workers into attached and unattached unemployed produces endogenous binary wage dispersion. The decentralized equilibrium with a Hosios value of the bargaining power is no longer constrained efficient: when changing attachment workers impose a negative externality on their former employer originating from a loss of the recall option. This inefficiency tends to produce excessive job creation. The paper also investigates returns to job mobility in Germany and shows that being recalled to the previous employer as opposed to the new job is associated with about 8% lower probability of wage improvement.
Keywords: Search equilibrium, temporary layoff, constrained efficiency, wage dispersion; 330; J23; J31; J63; M51